ANALYSIS OF INTERNAL CONTROL OF FIXED ASSETS IN PT. LUMBUNG BERKAT INDONESIA - Makaluas, Jesella Lourina; Pontoh, Winston (ACCOUNTABILITY, 2018)
The presence of an internal control system of fixed assets that will assist management in supervising, monitors costs incurred when fixed assets are acquired until property, plant, and equipment are released. Adding or extending the useful life of fixed assets and assisting in increasing the operational contribution and productive capacity of the company's fixed assets maintain security, check the accuracy and correctness of data from the company's fixed assets. This study aims to determine the implementation of the structure of Internal Controls of Fixed Assets conducted in PT Lumbung Berkat Indonesia which is a type of construction company. The analysis method used is descriptive method. Data type is qualitative data with secondary data source. The result of the research shows that internal control in PT Lumbung Berkat Indonesia has not been effective yet. This is seen from the lack of separation of duties and responsibilities between the finance and accounting departments, the absence of an audit committee, never conducting tests and measurements on fixed assets. Any decision relating to fixed assets shall first be authorized by the President Director, but the company never conducts physical property checks and matching with fixed assets records. There is also no expenditure on capital and revenues. Depreciation method used is straight line depreciationÂ  and implemented continuously every year. However, the list of fixed assets of the company has not been up to date since the company only attaches fixed assets in the form of buildings and vehicles in the project (excluding vehicles and inventory in the office).Keywords: Internal Control, Fixed Assets.